An investigation into the use of Castable silica waste to produce green mortar - Malallah, Mohammed Abdul-Kareem; Mezaal, Ansam Mishaal; nafaa, Mohammed (Al-Salam Journal for Engineering and Technology, 2024)
Cement is a crucial engineering material, and the inclusion of some other substances can alter the characteristics of concrete. Due to the growing tendency to use cement more extensively, it has become imperative to utilize waste resources in order to manufacture environmentally friendly mortar or concrete. Due to the increasing need for eco-friendlier cementitious products, it is becoming increasingly important to assess the pozzolan activity index of prospective materials that can be used as substitutes for cement. The purpose of this research is to present a study that was carried out to evaluate the impact of castable silica waste (CSW) on the development of mortar strength, as well as the optimal usage of mortar CSW and the best substitution ratio in the creation of sustainable mortar. CSW, at three different weight percentages (10%, 20%, 30%), was used as a partial replacement for cement and added superplasticizer SP. A normal mortar using Ordinary Portland cement OPC was constructed to investigate the strength activity index. Cubic mortar samples were fabricated and examined at 7days and 28days. The strength of tests generally increases as the amount of castable silica waste CSW increases up to a certain point. Beyond this point, however, the strength values start to decline with the further addition of CSW. Among the four types of CSW mortars, the most effective amount of cement substitute is around 10%. This is higher than the other green mortars since increasing the amount of CSW decreases compressive strength. The primary objective of this research is to mitigate the carbon dioxide emissions generated by the cement industry and decrease environmentally detrimental waste by utilizing it as a partial substitute for cement.